On the Attempt to Unlock the Black Boxes of Science (1) - Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2018)
[only abstract in English; full article and abstract in Lithuanian]This study is an analysis of a sociological research about the scientific activities performed by natural scientists. It is composed of three parts: a critical overview of Bruno Latour’s theoretical writings on the Actor-Network Theory, the description of the research and reflections on the findings. The research discussed in this study was a didactical experiment consisting of focus group discussions. The aim of the experiment was to facilitate an epistemological rupture, which, in the science studies, might be interpreted as a shift from the sociology of the social to the sociology of translation or the Actor-Network Theory treating non-social objects of nature, nonhumans or things as social entities within associations and networks. The sociology students who participated in the didactical experiment were very positive about their experience regarding the epistemological rupture and its role in shaping their knowledge about sociology itself. In this issue, we publish the first part of the study and discuss the ideas of B. Latour on the sociology of transduction and science studies.
Keywords: sociology of science and technology, actor-network theory, didactics of sociology, epistemological rupture